PROLIFERATION OF OIL PALM (Elaeis guineensis Jacq.) EMBRYOGENIC CALLUS WITH REPEATED SUBCULTURES IN LIQUID MEDIUM - Karyanti, Karyanti; Tajuddin, Teuku; Khairiyah, Hayat; Purwoko, Devit; Sukarnih, Tati; Rahmadara, Gemilang; Hanifah, Nurul Fitri; Rudiyana, Yayan; Kitagawa, Sayuri; Mira, Farida Rosana; Saga, Hirohisa (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2021)
The availability of high-quality seeds is now a necessity. This is due to a government program to replace oil palm trees in smallholder plantations with high quality seeds. An efficient protocol to produce a large number of embryos is needed. To increase the number of embryogenic callus production, the callus proliferation experiment was carried out through suspension culture. This study aimed to examine the proliferation ability of embryogenic callus from three different oil palm clones, in several repeated subcultures. Liquid MS media added with 1 ppm 2.4-D and 0.1 ppm NAA were used. Embryogenic callus was weighed by 0.1 - 0.2 g, transferred into the liquid media, shaking at 60-80 rpm and 27 ºC for 8 weeks without light. Continues subcultures were repeated up to 7 times. The results showed that the growth rate of embryogenic callus increased in the third and fourth subcultures and then decreased in subsequent subcultures. It also revealed that the entire embryogenic callus from the first subculture up to seventh subculture still has the ability to regenerate into new plants. These results indicate that oil palm embryogenic callus can be proliferated by suspension culture with a limit up to the fourth subculture. Ketersediaan benih kelapa sawit berkualitas saat ini merupakan kebutuhan karena adanya program pemerintah untuk menggantikan tanaman sawit di kebun-kebun petani. Salah satu cara vegetatif yang dapat dilakukan adalah meningkatkan jumlah kalus embriogenik yang dihasilkan melalui pengembangan kultur suspensi. Penelitian ini bertujuan mengkaji kemampuan proliferasi kalus embriogenik dari tiga klon kelapa sawit, pada beberapa kali subkultur yang berulang. Media cair MS dengan penambahan 1 ppm 2,4-D dan 0,1 ppm NAA digunakan untuk memperbanyak 0,1–0,2 g kalus embriogenik, dikocok pada 60-80 rpm dan suhu 27 ºC tanpa cahaya selama 8 minggu. Subkultur berulang dilakukan hingga 7 kali. Hasil percobaan menunjukkan bahwa kemampuan proliferasi kalus dipengaruhi oleh genotip tanaman induk. Rata-rata kalus embriogenik dapat meningkat pada subkultur ke-3 dan ke-4 dan semakin menurun pada subkultur selanjutnya. Kalus embriogenik hasil proliferasi subkultur pertama hingga ke-7 dapat tumbuh menjadi calon tanaman baru. Hasil ini menunjukkan bahwa kalus embriogenik kelapa sawit dapat diperbanyak dengan kultur suspensi pada batas sampai subkultur ke-4.